Forecasting interest rates using geostatistical techniques - Giuseppe Arbia; Michele Di Marcantonio (Econometrics, 2015)
Geostatistical spatial models are widely used in many applied fields to forecast data observed on continuous three-dimensional surfaces. We propose to extend their use to finance and, in particular, to forecasting yield curves. We present the results of an empirical application where we apply the proposed method to forecast Euro Zero Rates (2003-2014) using the Ordinary Kriging method based on the anisotropic variogram. Furthermore, a comparison with other recent methods for forecasting yield curves is proposed. The results show that the model is characterized by good levels of predictions' accuracy and it is competitive with the other forecasting models considered.
Keywords: C3; C53; E43; E47; 330; term structure; yield curve; forecasting; geostatistics; variogram; Ordinary Kriging